2018
DOI: 10.1108/intr-05-2017-0212
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing key influences of tourists’ acceptance of online reviews in travel decisions

Abstract: Journal: Internet Research PurposeThis study aims to examine what influence travelers' adoption of online reviews, and whether the online reviews will influence their travel planning decisions.Design/methodology/approach Data was collected from 193 respondents from eWOM websites and analyzed using structural equation modeling. FindingsOur results revealed that eWOM has a significant influence on travel decisions. Furthermore, travelers were willing to adopt information from eWOM and this information was useful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
103
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(111 citation statements)
references
References 70 publications
8
103
0
Order By: Relevance
“…In the three columns, there are keywords related to positive feelings (e.g., good, great). The crowdedness-related keywords crowd/s/ed/ing (7386), overcrowd/ed/ing (186), busy (2623), line/s (3392), queue/s (1139), wait/ed/ing (5243), and await/ing (72), together with ticket/s/ing (8563), and the dirtiness-related keywords abandoned (79), derelict (11), dirty (293), garbage (53), junk (101), rubbish (51), ruined (230), and trash (75), together with graffiti (420), that may indicate sustainability problems, appear in the attractions column. The riskiness-related keywords crime/inal/inally (103), danger/ous (122), pick pocket pickpocket/s (422), robbed robbery (66), steal stole/n (416), and thief/ves (97) also appear in the attractions column.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the three columns, there are keywords related to positive feelings (e.g., good, great). The crowdedness-related keywords crowd/s/ed/ing (7386), overcrowd/ed/ing (186), busy (2623), line/s (3392), queue/s (1139), wait/ed/ing (5243), and await/ing (72), together with ticket/s/ing (8563), and the dirtiness-related keywords abandoned (79), derelict (11), dirty (293), garbage (53), junk (101), rubbish (51), ruined (230), and trash (75), together with graffiti (420), that may indicate sustainability problems, appear in the attractions column. The riskiness-related keywords crime/inal/inally (103), danger/ous (122), pick pocket pickpocket/s (422), robbed robbery (66), steal stole/n (416), and thief/ves (97) also appear in the attractions column.…”
Section: Resultsmentioning
confidence: 99%
“…Another, on visitors from New Zealand [52], revealed that perceived usefulness and empowerment led to the use of TGC to plan the trip. A third, about Chinese travellers [53], showed that eWoM had a significant utility and influence in the planning and decision making related to the trip. The influence of OTRs in travel decision making has also been demonstrated through artificial intelligence methodologies [54].…”
mentioning
confidence: 99%
“…6). The relationship between the above variables and consumers' adoption of eTourism technology has been supported in many eTourism research (e.g., Chong et al 2018;Kim 2016;Chang et al 2016).…”
Section: Tam++ Models Technology Acceptance Model (Tam)mentioning
confidence: 90%
“…In the information management and marketing literature focusing on the antecedents of ORH, the term online review usefulness seems to be used in a broad (and sometimes loose) way and relates to the extent to which an OR is perceived as useful by consumers, sometimes with perceived usefulness measured as one of the core constructs/variables of an acceptance or adoption model such as the technology acceptance model [25,26] and its subsequent variations [139]. As such, usefulness pertains to online consumers' expectations that using ORs will enhance their performance in information seeking, which becomes a driver of consumers' attitude and intention to use ORs themselves [9,10,20,31].…”
Section: Orh and Financial Performancementioning
confidence: 99%